1999
DOI: 10.1002/jppr1999294196
|View full text |Cite
|
Sign up to set email alerts
|

Extemporaneous Dispensing: Opinions of Victorian Community Pharmacists

Abstract: Objectives: To determine estimates ofthe type and extent of extemporaneous dispensing undertaken by Victorian community pharmacists and to analyse their views on related issues. Study Procedure: After telephone contact, a survey was mailed to every third community pharmacy in Victoria (n = 420). Results: Completed surveys were received from 296 premises (70.5%). 1. Sample: 71% male; 61% sole/partner proprietor; 35% PhC and 67% BPharm graduates. 2. Extent: 60% dispensed 1-5 extemporaneous prescriptions per week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
(2 reference statements)
1
10
0
Order By: Relevance
“…McPherson et al (2010) found that physicians frequently consulted the compounding pharmacist about aspects of formulation, pharmaceutical presentation and compounded options as part of a collaborative prescribing process [52]. A high level of interest in and support for pharmacy compounding was also reported by in a survey of general practitioners in Australia [53]. Again, although limited by regional sampling and potential non-response bias, a study on the attitudes of medical specialists in Atlanta (USA), had similar results in that prescribers had a positive attitude towards compounding and the compounding pharmacist's ability and knowledge to participate in prescribing decisions [54].…”
Section: Re-emergence Of Extemporaneous Compoundingmentioning
confidence: 84%
“…McPherson et al (2010) found that physicians frequently consulted the compounding pharmacist about aspects of formulation, pharmaceutical presentation and compounded options as part of a collaborative prescribing process [52]. A high level of interest in and support for pharmacy compounding was also reported by in a survey of general practitioners in Australia [53]. Again, although limited by regional sampling and potential non-response bias, a study on the attitudes of medical specialists in Atlanta (USA), had similar results in that prescribers had a positive attitude towards compounding and the compounding pharmacist's ability and knowledge to participate in prescribing decisions [54].…”
Section: Re-emergence Of Extemporaneous Compoundingmentioning
confidence: 84%
“…A 1999 Australian study, 3 and an unpublished 2000 study conducted by Smith et al 4 in New Zealand (using the same survey instrument) have confirmed that the dispensing of such products has declined over the years. It was found that these products only represent one to two per cent of community pharmacies' total prescription volume.…”
Section: Introductionmentioning
confidence: 58%
“…The transition from the use of botanical to synthetic products, and the development of proprietary medicines, resulted in the decline of production of extemporaneous products/ although they continue to be available (albeit in smaller numbers) on the Pharmaceutical Benefits Scheme (PBS). A 1999 Australian study, 3 and an unpublished 2000 study conducted by Smith et al 4 in New Zealand (using the same survey instrument) have confirmed that the dispensing of such products has declined over the years. It was found that these products only represent one to two per cent of community pharmacies' total prescription volume.…”
Section: Introductionmentioning
confidence: 88%
“…These findings are in agreement with Pappas, and a recently published survey of the prevalence of compounding in the US. 15,16 The responses to questions about demographic factors such as gender, qualifications, PhARIA class, prescription volume, turnover, pharmacy size, staffing levels and Quality Care Pharmacy Program accreditation were similar to those reported by Dunphy et al, Berbatis et al and the Pharmacy Guild of Australia and indicate that the sample was representative of pharmacies in Australia. 13,14,17 One of the limitations of this study was that a self-reported survey instrument was used and the reliability of responses was not able to be independently checked.…”
Section: Discussionmentioning
confidence: 83%
“…15 Our survey found that the majority of pharmacies dispensed less that 1% of prescriptions extemporaneously but that almost all pharmacies prepared extemporaneous products. These findings are in agreement with Pappas, and a recently published survey of the prevalence of compounding in the US.…”
Section: Discussionmentioning
confidence: 97%